Use of patient-centred outcome measures alongside the personal wheelchair budget process in NHS England: A mixed methods approach to exploring the staff and service user experience of using the WATCh and WATCh-Ad. - Lorna Tuersley; Naa Amua Quaye; Kalpa Pisavadia; Rhiannon Tudor Edwards; Nathan Bray (PLoS ONE)
Background and objective Personal wheelchair budgets (PWBs) are offered to everyone in England eligible for a wheelchair provided through the National Health Service (NHS) to support their choice of equipment. The WATCh (Wheelchair outcomes Assessment Tool for Children) and related WATCh-Ad for adults are patient-centred outcome measures (PCOMs) developed to help individual users express their main outcome needs when obtaining a wheelchair and rate their satisfaction with subsequent outcomes after receiving their equipment. Use was explored in a real-world setting, aiming to produce guidance for use alongside the PWB process. Methods Three wheelchair service provider organisations across four sites participated. Staff and users completed surveys about their experience of assessments using the WATCh and/or WATCh-Ad. Selected patients were interviewed after receipt of their equipment, and staff were interviewed after experiencing a number of assessments. Thematic analysis was undertaken using the tool, survey and interview data. Results of pre- and post-equipment provision were presented graphically. Results Information on 75 assessments by 15 staff was obtained. Three-quarters of users or their carers rated the use of the tools in the assessment process as 'helpful' or 'very helpful'. Staff reported that the WATCh or WATCh-Ad had been considered 'useful' in developing individual care plans in around 1 in 3 cases and affected the prescription in 1 in 4 cases. Concerns were expressed about the length of time taken to administer the tools in clinic. However, some staff noted this reduced with more hands-on experience and by providing the tools to users in advance of the appointment. Conclusions The WATCh and WATCh-Ad PCOMs are suitable for routine use by wheelchair service providers to assist the assessment process. It is recommended that tool materials are provided in advance to users/carers and that staff are allowed time to develop their ways of working with them.